2020 IEEE International Conference on Blockchain (Blockchain) 2020
DOI: 10.1109/blockchain50366.2020.00011
|View full text |Cite
|
Sign up to set email alerts
|

CoinWatch: A Clone-Based Approach For Detecting Vulnerabilities in Cryptocurrencies

Abstract: Cryptocurrencies have become very popular in recent years. Thousands of new cryptocurrencies have emerged, proposing new and novel techniques that improve on Bitcoin's core innovation of the blockchain data structure and consensus mechanism. However, cryptocurrencies are a major target for cyber-attacks, as they can be sold on exchanges anonymously and most cryptocurrencies have their codebases publicly available. One particular issue is the prevalence of code clones in cryptocurrencies, which may amplify secu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Besides these works, three recent studies focused on the Bitcoin patch delay analysis that is most related to BlockScope's Calculator component. Specifically, CoinWatch [42] used four CVEs of Bitcoin to test and analyze the delay of many old Bitcoin's forked projects that are no longer maintained. It used the Simian the clone detector [1], i.e., simple string match, to detect only Type-1 clones.…”
Section: Related Workmentioning
confidence: 99%
“…Besides these works, three recent studies focused on the Bitcoin patch delay analysis that is most related to BlockScope's Calculator component. Specifically, CoinWatch [42] used four CVEs of Bitcoin to test and analyze the delay of many old Bitcoin's forked projects that are no longer maintained. It used the Simian the clone detector [1], i.e., simple string match, to detect only Type-1 clones.…”
Section: Related Workmentioning
confidence: 99%
“…However, unlike Li et al's work [19], we identified the locations of those vulnerabilities and patches in Bitcoin derivatives using their source code as well as Git commits because we wanted to also cover the cases where patch information is not reported through Git commits. Hum et al [14] used clone-code detection to find vulnerable crypto projects, and discovered 786 vulnerabilities from 384 projects using 4 CVEs (CVE-2018-17144, CVE-2016-10724, CVE-2016-10725, and CVE-2019-7167). In this paper, we report a much more efficient vulnerable code detection method: we use code commits to inspect code changes only, rather than examining the full source code.…”
Section: Related Workmentioning
confidence: 99%
“…Despite focusing on different aspects than security, the authors suggest that code similarity might indicate inherited vulnerabilities. In [23], Hum et al propose a code evolution technique and a clone detection technique to indicate which cryptocurrencies are vulnerable once a vulnerability has been discovered. However, similar to all GitHub parsers, these techniques cannot infer when a given patch has been ported onto an altcoin in case of rebase operations since such timestamps are overwritten by rebase.…”
Section: Related Workmentioning
confidence: 99%